1985
DOI: 10.1002/clc.4960081205
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise training and diet modification on serum lipids and lipoproteins in coronary artery disease patients treated with thiazides

Abstract: Summary:The effects of chronic exercise training and diet modification on serum lipids and lipoproteins were measured in 17 hypertensive males and 41 normotensive males with documented coronary artery disease (CAD). Exercise consisted of aerobic activities which were performed at approximately 75-85 % of the symptom-limited maximum heart rate for 30-40 minutes, three times weekly for 3 months. Each participant's diet was also controlled, the recommended daily intake of fat and cholesterol was no more than 40 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Furthermore, studies of higher frequency of exercise per week or longer duration of exercise training, demonstrated differential findings [30,31]. Indeed, Kahrs et al [23] opined that higher exercise intensities and longer intervention periods may be necessary to elicit the desired changes in serum lipid levels.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Furthermore, studies of higher frequency of exercise per week or longer duration of exercise training, demonstrated differential findings [30,31]. Indeed, Kahrs et al [23] opined that higher exercise intensities and longer intervention periods may be necessary to elicit the desired changes in serum lipid levels.…”
Section: Discussionmentioning
confidence: 95%
“…Kahrs et al [23] reported a decrease in triglyceride after a 12-week vigorous intensity aerobic exercise and diet modification in individuals with coronary heart disease on thiazides. However, Kahrs et al [23] did not find a significant reduction in LDL-C.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Training may be beneficial in counteracting the increase of serum lipids frequently induced by diuretics as shown by Kahrs et al [1985],…”
mentioning
confidence: 99%